Computer networks : a top-down approach - Forouzan, Behrouz A.; Mosharraf, Firouz (New York : McGraw-Hill, 2012)
Offers an explanation of the application layer, helping students to understand how network devices work, and discusses the other layers, ending with the physical layer
1. Introduction -- 2. Application layer -- 3. Transport layer -- 4. Network layer -- 5. Data link layer: wired networks -- 6. Wireless networks and mobile IP -- 7. Physical layer and transmission media -- 8: Multimedia -- 9. Network management -- 10. Network security -- 11. Socket-interface programming in Java
Includes bibliographical references (p. 901-904) and index
Keywords: Computer networks; Internet